Investigation on machining copper plates with NiP coated tools using tailor-made micro-electro discharge machine. Issue 4 (2nd October 2017) - Hiremath, Somashekhar S.; Raju, Leera
Abstract: Micro-Electro Discharge Machining (μ-EDM) is one of the high precision non-conventional machining methods used for the generation of micro sized features like microholes, microchannels, microstructures etc. on any conducting engineering materials with no constraints on hardness and fragileness. In the present work, experiments have been carried out to machine microholes on copper plates using NiP coated hollow copper tool electrodes. The process parameters selected for the study are voltage, capacitance, pulse on- time and coating thickness and studied their effect on Material Removal Rate (MRR), Tool Wear Rate (TWR), Diametral OverCut (DOC), and Taper Angle (TA). Taguchi L16 orthogonal array experimental plan has been selected to conduct the experiments systematically. Signal-to-Noise ratios and ANalysis Of VAariance (ANOVA) was used to determine the statistically significant factors influencing the process response. ANOVA results indicate that voltage is the most influencing parameter on all output responses. Grey Relational Analysis (GRA) was utilized to determine the optimal combination of μ-EDM parameters used to increase the MRR and simultaneously to minimize the tool wear, the overcut and the taper angle. From the GRA analysis the optimum parameter combination for maximizing MRR and minimizing the TWR, DOC and TA are voltage: 22 V, capacitance: 330 μF, pulse on-time: 120 μs and coating thickness: 10 μm. Response Surface Methodology (RSM) was also carried out to study the effect of interaction between two input parameters on performance characteristics – MRR, TWR etc. The empirical models for each response criteria were obtained using the RSM with the aid of statistical software.